Institutions matter: let knowledge make the difference (Road Map 2002 - 2006) - International Service for National Agricultural Research (International Service for National Agricultural Research, 2001)
Agriculture is undergoing rapid changes in developing countries. Globalization, trade liberalization, the changing role of government in society, the growing concerns for environmental protection, climate change, and biotechnology all present important challenges for the agricultural sector. Young people are taking up new endeavors, and as an increasing number of young men migrate to find work in towns and cities, many of the farmers are now female, combining farming with their many other tasks and chores. In many countries the HIV-AIDS pandemic is taking a heavy toll on young adults, leaving the very old and the very young to farm the land or fish the seas. The result is that indigenous agricultural knowledge is increasingly resting with the older generation. Global staple foods have fallen in price over the last 20 years, and food shortages are now more often caused by wars, political instability, and poverty than by a lack of production capacity. Worldwide, 750 million people are underfed, and many households have inadequate purchasing power to acquire sufficient food, even where it is available in local markets. To overcome problems of food scarcity and malnutrition, food must become more widely available in developing regions.